Socio-economic foundations of legal regulation of modern integration processes - Ivanova A. V. (Socio-Economic Processes of Modern Society, 2024)
The article examines the basic principles of legal regulation of modern integration processes involving the Russian Federation, and notes their socio-economic foundations. This article allows us to expand our understanding of how legal regulation of integration processes of varying depth and intensity is carried out.
Keywords: legal regulation; интеграционные процессы; integration processes; правовая интеграция; правовая регламентация; legal integration